1993
DOI: 10.1159/000267282
|View full text |Cite
|
Sign up to set email alerts
|

Electroretinographic Response in WAG/Rij Rats after Low-Intensity Cyclic Light Exposure

Abstract: In order to investigate the combined influence of age and light, the b-wave and oscillatory potentials (OPs) of the electroretinogram (ERG) were recorded in 1.5-, 7- and 12-month-old WAG/Rij rats, reared under homogenous low-intensity cyclic light exposure. Wistar albino rats of the same ages, reared under the same conditions, served as controls. The b-wave amplitude decreased, and its implicit time increased in the older age groups significantly more in WAG/Rij than in Wistar rats. Statistical analysis indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…A reduction in ERG amplitudes with age has also been shown previously for both pigmented and nonpigmented mice and rats (e.g. Cillino et al, 1993;Li et al, 2001).…”
Section: Rod Erg Analysis In Pigmented and Albino Animals During Matusupporting
confidence: 78%
See 1 more Smart Citation
“…A reduction in ERG amplitudes with age has also been shown previously for both pigmented and nonpigmented mice and rats (e.g. Cillino et al, 1993;Li et al, 2001).…”
Section: Rod Erg Analysis In Pigmented and Albino Animals During Matusupporting
confidence: 78%
“…These possibilities, however, cannot be distinguished with the present data. Our results differ from data obtained from guinea pigs in which albino guinea pigs had faster responses than pigmented animals (Vingrys & Bui, 2001), but correlates with data obtained by multifocal ERGs from albino and pigmented rats showing that response latency is increased and amplitude reduced in albino rats (Ball & Petry, 2000), and obtained by single-flash ERGs from albino rats demonstrating that b-wave latency increased with age (Cillino et al, 1993). These differences between various rodents have yet to be addressed.…”
Section: Rod Erg Analysis In Pigmented and Albino Animals During Matusupporting
confidence: 49%
“…et al (1980) [3,4] reported, that retinal degeneration in Waj/Rij rats resembles RP temporally and morphologically. In WAG/Rij rat, reared under homogenous lowintensity cyclic light exposure, the b-wave amplitude of electroretinogram decreased, and its implicit time increased in the older age groups significantly more than in Wistar rats [5] . Prolonged implicit time and decreased b-wave amplitude of electroretinogram were shown in most RP cases compared with that in normal eyes [6] .…”
Section: Introductionmentioning
confidence: 84%